Polarization-maintaining buffered Fourier domain mode-locked swept source for optical coherence tomography - Zhang, Jun; Jing, Joe; Wang, Pinghe; Chen, Zhongping (Optics letters, 2011)
A polarization-maintaining buffered Fourier domain mode-locked (FDML) swept source with a center wavelength of 1300 nm is demonstrated. The scanning rate of the buffered FDML swept source is doubled without sacrificing the output power of the swept source by combining two orthogonally polarized outputs with a polarization beam combiner. The stability of the swept source is improved because the polarization state of the laser beam inside the laser cavity is maintained without the use of any polarization controllers. The swept source is capable of an edge-to-edge tuning range of more than 150 nm and a FWHM range of 95 nm at a 102 kHz sweeping rate and with an average power of 12 mW. A swept source optical coherence tomography (SSOCT) system is developed utilizing this buffered FDML swept source. The axial resolution of the SSOCT system is measured to be 9.4 µm in air. The sensitivity of the SSOCT system is 107.5 dB at a depth of 0.25 mm with a 6 dB roll-off at a depth of 2.25 mm.